The Principal's Leadership in Automatizing Religious Culture in the Vocational High School Khoriyah Hasyim Jombang - Saefrudin, Saefrudin (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2024)
The existence of the Khoriyah Hasyim Vocational High School is one of the schools that carries out many religious activities. The existence of gaps in behavior (attitudes) among students requires educational institutions to be more active in developing religion. The formation of attitudes and personality attracts people and becomes an image for several schools. Therefore, with proper implementation, the process of realizing a school religious culture will become easier and more systematic. The aim of this research is to: (1) analyze the basis for the development of religious culture at Khoriyah Hasyim Vocational School Jombang, (2) analyze the implementation of religious culture development at Khoriyah Hasyim Vocational School Jombang, (3) analyze the implications of the principal's leadership for the development of religious culture at Khoriyah Vocational School Hasyim Jombang. The approach in this research uses qualitative research with a descriptive analytical case study approach. This research results in (1) the basis for developing religious culture at SMK Khoriah Hasyim Tebuireng Jombang, namely; environmental support, competent teachers, and based on five principles, namely; sincere, honest, responsible, hard work and tolerance. (2) implementation of religious culture development at Khoriyah Hasyim Tebuireng Jombang Vocational School